IMPLEMENTATION OF VILLAGE FINANCIAL ADMINISTRATION: PROCEDURES IN THE MANAGEMENT OF VILLAGE FUNDS IN ACEH - Cut Zira Miranda; Cut Intan Amalia; Agustina (Az-Zahra Media Society, 2026)
This study aims to analyze the implementation of gampong financial administration procedures in the management of Village Funds in Aceh and to examine their impact on accountability and transparency. The management of Village Funds is an essential component of rural development that requires the application of good governance principles, namely transparency, accountability, participation, as well as orderliness and discipline in budgeting, as stipulated in the Regulation of the Minister of Home Affairs Number 20 of 2018. The implementation of financial administration procedures includes the stages of planning, implementation, administration, reporting, and accountability, which must be carried out consistently by gampong officials.The results of the study indicate that the proper implementation of financial administration procedures has a positive effect on improving accountability and transparency. Therefore, it is necessary to enhance the capacity of gampong officials, as well as strengthen community participation and supervision systems in order to achieve more effective, transparent, and accountable village financial governance. However, several challenges are still encountered, including limited competence of officials, suboptimal utilization of the Village Financial System (SISKEUDES), and low levels of information transparency to the public.